Prelove Outwear / Muhammad Ammar Haziq Arizuddin, Muhammad Idham Abdul Ghani and Muhammad Iqbal Hakimi Ismail - Arizuddin, Muhammad Ammar Haziq; Abdul Ghani, Muhammad Idham; Ismail, Muhammad Iqbal Hakimi (2021)
Prelove Outwear is a company operating in a small to medium industry and also involved in the fashion industry. The company name was chosen because it is attractive and easily recognizable by anyone. Our company also has our own motto which is Cheap & Stylish which shows our clothes are available at cheap and economical prices as well as helping customers to be stylish. Our company's main aim is to provide our clients with good service. By being in contact and seeking input from our clients, we aim to build successful customer relationships. Our company consists of 10 staff consisting of General Manager, Marketing Manager, Financial Manager, Operational Manager, Marketing Assistance, Financial Assistance and Worker. With the skills available to the staff, we encourage our strength to achieve the company's objectives. Teamwork, debate and interaction are the keys to our success. Prelove Outwear is an online company that operates on the platform of the digital domain. This company is determined to function as an online company. The reason why 'Prelove Outwear' is an online company is that it can save physical space and leasing costs, users can access the online store anytime and anywhere, and the business can be run anywhere by the shop owner. While planning this business, we managed to analyse some information about this business in terms of administrative plans, marketing plans, operating plans, and financial plans.